Neuroprotective effects of hesperidin and auraptene on 6-hydroxydopamine-induced neurodegeneration in SH-SY5Y cells - Malihe Mehrparvar Tajoddini; Elaheh Gheybi; Mehdi Rostami; Seyed Hadi Mousavi; Seyed Isaac Hashemy; Roghayeh Rashidi; Mohammad Soukhtanloo (Avicenna Journal of Phytomedicine)
Objective: Destruction of dopaminergic neurons causes diseases. Various compounds with neuroprotective and antioxidant properties have been identified, including Hesperidin (HES) and Auraptene (AUR). We aimed in this study to evaluate the in vitro protective effects of these compounds in SH-SY5Y neuroblastoma cell line against the induced neurotoxicity of 6-hydroxydopamine (6-OHDA).Materials and Methods: The MTT test to assess cell viability was used. Flow cytometry was conducted for the cell cycle analysis using propidium iodide (PI) stain. The intracellular production of reactive oxygen species (ROS) was assessed using 2, 7′-dichlorofluorescein diacetate (DCFDA) probe and fluorimetry.Results: Following 6-OHDA treatment, cell viability decreased, and G2/M arrest and ROS levels increased. Our intervention demonstrated that only HES has neuroprotective effects against 6-OHDA-induced toxicity.Conclusion: HES protects SH-SY5Y cells against 6-OHDA-induced neural damage via inhibiting G2/M arrest, reducing the amount of ROS, and increasing cell viability. However, the different effects and more precise mechanisms are still unknown, and requires new research on animal and human models.